2016
DOI: 10.1086/684223
|View full text |Cite
|
Sign up to set email alerts
|

Coupling freshwater mussel ecology and river dynamics using a simplified dynamic interaction model

Abstract: Freshwater faunal diversity and abundance have declined dramatically worldwide, concurrent with changes in streamflow and sediment loads in rivers. Cumulative effects and interdependencies of chronic covarying environmental stressors can obscure causal linkages that may be controlling the population dynamics of longer-lived freshwater fauna, such as mussels. To understand changes in long-term mussel population density, we developed a dynamic, process-based interaction model that couples streamflow, suspended s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 76 publications
1
34
0
Order By: Relevance
“…Hansen et al. () found that mussels provide important feedback on the chemical and physical environment and that there is a relationship between mussel density and the strength of this feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Hansen et al. () found that mussels provide important feedback on the chemical and physical environment and that there is a relationship between mussel density and the strength of this feedback.…”
Section: Discussionmentioning
confidence: 99%
“…As part of an NSF‐funded Water Sustainability and Climate interdisciplinary project focused in the predominantly agricultural MRB (a 44,000 km 2 basin included in the Gupta et al's study area), we have begun a comprehensive effort aimed at quantifying the hydrologic changes and the cascade of these changes from hydrology to sediment production and transport, to nutrient and phosphorous cycling, to river ecology [e.g., Foufoula‐Georgiou et al ., ; Schaffrath et al ., ; Hansen et al ., ]. In terms of hydrologic change, our analysis of daily streamflow has clearly demonstrated the effects of LULC on the daily hydrologic response.…”
mentioning
confidence: 80%
“…Human impacts are largely to blame for the massive decline in freshwater mussel populations, and have imposed pressures upon catchments both globally and locally, i.e. within the geographical distribution of L. bracteata (Bogan, ; Hansen et al, ; Howells, ; Lydeard et al, ).…”
Section: Introductionmentioning
confidence: 99%